BRCA Genetic Counseling Among At‐Risk Latinas in New York City: New Beliefs Shape New Generation. Issue 1 (15th August 2014) - Sussner, Katarina M.; Edwards, Tiffany; Villagra, Cristina; Rodriguez, M. Carina; Thompson, Hayley S.; Jandorf, Lina; Valdimarsdottir, Heiddis B.
Abstract: Despite the life‐saving information that genetic counseling can provide for women at hereditary breast and/or ovarian cancer (HBOC) risk, Latinas disproportionately underuse such services. Understanding Latinas' beliefs and attitudes about BRCA genetic counseling may be the key to better health promotion within this underserved, at‐risk group. We conducted 12 focus groups ( N  = 54) with at‐risk Latina women in New York City, followed by 30 in‐depth interviews among a subset of the focus group women. Both were professionally transcribed, translated where applicable and data analysis was completed by two coders trained in qualitative methods. Results revealed personal and community knowledge about BRCA genetic counseling was relatively low, although women felt largely positive about counseling. The main motivator to undergo genetic counseling was concerns about learning family members' cancer status, while the main barrier was competing demands. Generational differences were apparent, with younger women (approximately <55 years) reporting that they were more interested in educating themselves about counseling and other ways to prevent cancer. Younger women were also less likely to ascribe to traditionally Latino‐centered cultural beliefs which could serve as barriers (e.g. machismo, fatalismo, destino) to undergoing genetic counseling. Participants were largely enthusiastic about educational efforts to increase awareness of genetic counseling among Latinos. Revealing the beliefs and attitudes of underserved Latinas may help shape culturally appropriate educational materials and promotion programs to increase BRCA genetic counseling uptake within this underrepresented community.